Evidence-based practice in Chile. (26th April 2018) - Caneo, Constanza; Calderón, Jorge
Abstract : Over the past few decades, the emergence of evidence-based practice medicine (EBP) has allowed a change in the integration of knowledge with policy making and health service development, and Chile has been influenced by EBP with no exemption. In this paper, we will describe the impact of the EBP model at different levels of the Chilean health system, including the development of national clinical guidelines, medical training and in-patient involvement in health awareness.